PENGARUH PENGGUNAAN STEP UP VOLTAGE DENGAN VARIASI KONSENTRASI BIOETANOL DALAM PERTALITE TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR HONDA BEAT - Kolik Setyawan; Danar Susilo Wijayanto; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study with stationary test aims to (1) To investigate the effect of using step up voltage on Honda Beat motorcycles on fuel consumption with stationary test. (2) To investigate the variation of the best voltage from the use of step up voltage on the fuel consumption of Honda Beat 2013 motorcycles with stationary test. (3) To investigate the effect of the use of a mixture of bioethanol and pertalite fuels on the fuel consumption of Honda Beat motorcycles with stationary test. (4) To investigate the variation of the best concentration of mixing bioethanol in pertalite on the fuel consumption of a Honda Beat 2013 motorcycle with stationary test. (5) To investigate the best configuration of a mixture of bioethanol and the use of step up voltage on the fuel consumption of a Honda Beat motorcycle with stationary test. Data collection techniques are needed to obtain results. valid data from the tests that have been carried out. Experimental techniques were used to collect data from each of the variables studied. So that the determination of variables is very necessary by carrying out clear research and testing procedures in order to facilitate the process of collecting data from the results of these experiments. The test results on the stationary test, namely the use of step up voltage, there is an effect on fuel consumption, the best is set at voltage of 14,3 V at 3.65 ml/min. The use of variations in the concentration of bioethanol in pertalite has an effect on fuel consumption with the best results using a 20% bioethanol concentration of 4.56 ml/minute. The best configuration was obtained when the step up voltage was set at 14.1 V and the 25% bioethanol concentration was 4.01 ml/min. more perfect due to a decrease in the level of fuel consumption in the tested vehicle.